Over Review on Potential Use of Hydrogel in Cancer Treatment - Chothe, Chaitali; Rutuja shaha, Rutuja (Asian Journal of Pharmaceutical Research and Development, 2018)
ABSTRACT In this review study was carried out to focus on uses of hydrogels in cancer treatment. hydrogel has unique property due to which it has played a vital role in controlled-release drug delivery systems. A hydrogel has property of swelling in water and 3-D structure. In this review we have focuses on use of hydrogel specifically in breast cancer, metastatic cancer,use of hydrogel in Transdermal drug delivery. hydrogels facilitate the modern and improved prospects for the treatment of cancer with minimum cytotoxic effects to the healthier cells or tissues. in the text we have overviewed about types and methods of hydrogel preparation. we have conclude with the help of hydrogel we can increase the potentiality and patient compliance in treatment of cancer ,also it possible to come over few side effects.